Fallopian tube secreted protein affects ovarian metabolites in high grade serous ovarian cancer - Bergsten, Tova M.; Levy, Sarah E.; Zink, Katherine E.; Lusk, Hannah J.; Pergande, Melissa R.; Cologna, Stephanie M.; Burdette, Joanna E.; Sanchez, Laura M. (Frontiers in Cell and Developmental Biology, 2022)
High grade serous ovarian cancer (HGSOC), the most lethal histotype of ovarian cancer, frequently arises from fallopian tube epithelial cells (FTE). Once transformed, tumorigenic FTE often migrate specifically to the ovary, completing the crucial primary metastatic step and allowing the formation of the ovarian tumors after which HGSOC was originally named. As only the fimbriated distal ends of the fallopian tube that reside in close proximity to the ovary develop precursor lesions such as serous tubal intraepithelial carcinomas, this suggests that the process of transformation and primary metastasis to the ovary is impacted by the local microenvironment. We hypothesize that chemical cues, including small molecules and proteins, may help stimulate the migration of tumorigenic FTE to the ovary. However, the specific mediators of this process are still poorly understood, despite a recent growth in interest in the tumor microenvironment. Our previous work utilized imaging mass spectrometry (IMS) to identify the release of norepinephrine (NE) from the ovary in co-cultures of tumorigenic FTE cells with an ovarian explant. We predicted that tumorigenic FTE cells secreted a biomolecule, not produced by non-tumorigenic cells, that stimulated the ovary to release NE. As such, we utilized an IMS mass-guided bioassay, using NE release as our biological marker, and bottom-up proteomics to demonstrate that a secreted protein, SPARC, is a factor produced by tumorigenic FTE responsible for enhancing release of ovarian NE and influencing primary metastasis of HGSOC. This discovery highlights the bidirectional interplay between different types of biomolecules in the fallopian tube and ovarian microenvironment and their combined roles in primary metastasis and disease progression.